2019 IEEE PES Innovative Smart Grid Technologies Europe (ISGT-Europe) 2019
DOI: 10.1109/isgteurope.2019.8905490
|View full text |Cite
|
Sign up to set email alerts
|

Implicitly Modeling Frequency Control within Power Flow

Abstract: In this paper, we extend a circuit-based, current-voltage power flow formulation to include frequency deviations and implicitly model generator primary and secondary control actions as a function of their temporal dependence. This includes extending the slack bus generator model(s) to better represents its true behavior with frequency controls. These implicit models obviate the need for outer iteration loops and improve the robustness of the simulation convergence when frequency deviations are considered. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…To address the problem of distributing the incremental powers after the occurrence of disturbance, some contributions propose different criteria. In [3] and [16] the generator power mismatches implicitly contain the presence of the frequency deviation. In [17], participation factors are obtained by considering the costs of generating units, thus, implementing an economic dispatch of the power unbalance.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…To address the problem of distributing the incremental powers after the occurrence of disturbance, some contributions propose different criteria. In [3] and [16] the generator power mismatches implicitly contain the presence of the frequency deviation. In [17], participation factors are obtained by considering the costs of generating units, thus, implementing an economic dispatch of the power unbalance.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…In [10] and [17], we have shown that convergence issues due to piecewise discontinuous modeling of limits can be avoided by using implicit models for system control including real power control of a generator based on frequency deviations. It was shown that a generator's change in real power due to the primary response can be captured by formulating the change in real power as a function of frequency including real power limits [18]. This continuous model implicitly captures the generator real power limits without the need for outer iteration loops.…”
Section: A Governor Power Flowmentioning
confidence: 99%